Monitoring Heart Disease and Diabetes with Mobile Internet Communications - David Mulvaney; Bryan Woodward; Sekharjit Datta; Paul Harvey; Anoop Vyas; Bhaskar Thakker; Omar Farooq; Robert Istepanian (International Journal of Telemedicine and Applications)
A telemedicine system is described for monitoring vital signs and general health indicators of patients with cardiac and diabetic conditions. Telemetry from wireless sensors and readings from other instruments are combined into a comprehensive set of measured patient parameters. Using a combination of mobile device applications and web browser, the data can be stored, accessed, and displayed using mobile internet communications to the central server. As an extra layer of security in the data transmission, information embedded in the data is used in its verification. The paper highlights features that could be enhanced from previous systems by using alternative components or methods.